2018
DOI: 10.1111/soc4.12568
|View full text |Cite
|
Sign up to set email alerts
|

Refugees as icons: Culture and iconic representation

Abstract: The September 2015 photograph of Alan Kurdi, a 3-year-old Syrian boy, lying facedown and dead on a Turkish beach, quickly became an iconic representation of Europe's "refugee crisis." Even though images of distant suffering of refugees have become ubiquitous, only a few become iconic. It is this cultural process of iconization that often bedevils sociologists interested in visuality. How does an image gain the necessary currency to sway public opinion or even policy making? Why do some photographs elicit profo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…Icons, by their nature, are material artifacts imbued with symbolic meanings and emotional resonance [Alexander 2010; Binder 2012; Kopper 2014; Binder and Jaworsky 2018]. They are objects or images that have become common cultural touchstones.…”
Section: An Icon In Common: a Sign Of Solidaritymentioning
confidence: 99%
“…Icons, by their nature, are material artifacts imbued with symbolic meanings and emotional resonance [Alexander 2010; Binder 2012; Kopper 2014; Binder and Jaworsky 2018]. They are objects or images that have become common cultural touchstones.…”
Section: An Icon In Common: a Sign Of Solidaritymentioning
confidence: 99%
“…For example, a famous photograph of a dead Syrian boy, Alan Kurdi, featured in the EP's migration discourse and was used in the arguments of human security discourse. Wikström (2015) stated: “It is our European decency that lies lifeless on the Turkish beach together with Alan Kurdi, the three‐year‐old toddler in his red T‐shirt and small sneakers.” The photograph of Kurdi became a “humanitarian icon” during the peak of the “migration crisis” (Binder & Jaworsky, 2018). Moreover, Westerners could easily perceive Kurdi as a victim who might have been their own child since he was dressed like a Western youngster and not in exotic clothes (Mortensen & Trenz, 2016).…”
Section: (Sub)categories Of Legitimation and Their Representationmentioning
confidence: 99%
“…When an image of a toddler named Alan Kurdi, who was found dead on a Turkish beach in September 2015 having drowned attempting to reach European shores, was widely published across news media, it stimulated significant academic interest in the visual representation of refugees. Binder and Jaworsky’s (2018) analysis of images of Alan Kurdi shows that such images have a profound effect on public attitudes towards refugees (see also Adler-Nissen et al, 2020; Mortensen, 2017), and wider research has shown the power of gendered visual portrayals of refugees in silencing women’s experiences (Amores et al, 2020) and criminalising men (Banks, 2011), as well as the mainstreaming of such imagery across news media (Wilmott, 2017).…”
Section: Refugees and The Tabloid News Mediamentioning
confidence: 99%